KNOWLEDGE OF NURSING PROFESSIONALS REGARDING PRESSURE ULCERS IN TWO SURGICAL UNITS - PART 1 - Nathalia Ingrid Crosewski; Débora de Sousa Lemos; Aline Batista Mauricio; Hellen Roehrs; Marineli Joaquim Meier (Universidade Federal do Paraná, 2015)
A case study was undertaken in a teaching hospital, in December 2012 - February 2013, aiming to identify the knowledge of the nursing professionals regarding pressure ulcers in two surgical units, with emphasis on aspects relating to prevention. A total of 25 nursing professionals participated, and a validated instrument was used which considers appropriate knowledge to be held by those who obtained 90% of correct answers or more. The mean for correct answers in the units was equal to 73.88%. The most common errors were: the concept of stage III of pressure ulcers and the indication of massage in regions of bony prominence, raising the bed to an angle greater than 30°, the use of gloves full of water, gel inflatable ring cushion, and the repositioning of seated patients. There is also evidence for the need for updating regarding the issue of pressure ulcers in accordance with the guidelines.